(untitled) (Raparin Journal of Humanities (RJH), 2020)
The research highlights the effects of the financial crisis on Media’s institutions in the Kurdistan Region. The research is excerpted from the Master’s thesis (The Impact of the Financial Crisis on the Financial Sources of Media Institutions in the Kurdistan Region) and it is a Media and Economic Subject at the same time The aim( goal) of the research : to show the extent of the impact of the financial crisis on the performance and how to work in medias institutions, according to the type of owner of the institution and the type of media. In order to reach the mentioned goal, the research used the survey method. In the process of collecting information, use the questionnaire (scale) by distributing it to employees and employees of Media’s organizations. The research consists of three main sections The first section: It consists of the research methodology The second section: It is the theoretical aspect of the research and consists of two issues. The first issue: The occurrence of the financial crisis in the Kurdistan Region, factors of its occurrence and its implications. The second issue: the financial sources of media organizations and their economic peculiarities. The third and last chapter: It is the practical and field aspect of the research, and it includes the results and suggestion.